Full-term pregnancy in a rudimentary horn with a live fetus: A case report. Issue 34 (21st August 2020) - Zhang, Yu; Pang, Yingxin; Zhang, Xue; Zhao, Zhe; Liu, Peishu
Abstract: Introduction: Rudimentary horns and unicornuate uteri, 2 types of Mullerian duct abnormalities, often lack obvious symptoms. Ultrasonography (US) and magnetic resonance imaging (MRI) are alternative examinations but have low accuracy. Full-term rudimentary horn pregnancies are rather rare but life-threatening. Patient concerns: A 30-year-old Chinese woman complained of lower abdominal pain one year after a full-term unicornate uterus pregnancy and a rudimentary horn pregnancy successively. Diagnosis: Uterine dysplasia (right rudimentary uterine horn and left unicornate uterus), hematometra and right fallopian tube effusion were diagnosed. Interventions: We performed laparoscopic hysterectomy (rudimentary horn), right salpingectomy, pelvic adhesion release and hysteroscopy. Outcomes: The patient has not complained of specific discomfort during the one-year follow-up so far. Conclusion: The reported case was a rare full-term rudimentary horn pregnancy. The degree of development of the rudimentary horn, such as the endometrial function, muscle layer thickness, and uterine shape and size, is closely related to pregnancy outcome. The rudimentary horn with a functional endometrium must be disposed of once it is definitely diagnosed. Pregnancy in the rudimentary horn with a weak muscular layer should be treated as soon as possible. Detailed and scientific prenatal examination is important.